VITAMIN D DEFICIENCY PANDEMIC, A REALITY OR AN OVER DIAGNOSIS? NEED TO RETHINK VITAMIN D DEFICIENCY CUT OFF LEVELS - Bibi, Afshan; Asif, Naveed; Haroon, Zujaja Hina; Ijaz, Aamir; Nawaz, Asif; Atif, Qurat Ul Ain (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine clinical decision limits (cut off points) for vitamin D deficiency based on secondary hyperparathyroidism. Study Design: Cross sectional study. Place and Duration of Study: This study was conducted in the Department of Chemical Pathology and Endocrinology, Armed Forces Institute of Pathology (AFIP), from Dec 2016 to May 2017. Methodology: One hundred and sixteen subjects, aged 18 to 60 years, of either gender, with vitamin D levels less than 50nmol/L, were consecutively included in the study. Results: Serum 25(OH) D had inverse relation with plasma iPTH level (r=-0.597, p<0.0001). Thirty five percent of the subjects with vitamin D level below 50nmol/L had secondary hyperparathyroidism. However, the frequency of secondary hyperparathyroidism was 52% in subjects with 25 (OH) D level less than 25nmol/L compared with 28% having serum vitamin D levels of 25-40nmol/L. None of the patient with Vitamin D level above 40nmol/L had secondary hyperparathyroidism. Receiver operating characteristic (ROC) curve showed that 25(OH) D level of 25.5nmol/L as an optimal cut off level for vitamin D deficiency based on Secondary Hyperparathyroidism with area under the curve (AUC) was 0.761. Conclusion: High frequency of secondary hyperparathyroidism in adults with vitamin D levels under 25nmol/L necessitates reconsideration of vitamin D cutoff limit for bone health.